The Impact of Intergenerational Reminiscences on University Students in Malaysia - Kok, Jin Kuan; Pheh, Kai-Shuen; Lee, Wan Ying (JPAIR Multidisciplinary Research, 2016)
As the aging population is growing rapidly in Malaysia, there is a need to enhance intergenerational communication to improve intergenerational understanding. Older people have accumulated vast experience in life, and their narrative sharing would be beneficial for younger generations. The purpose of the study is to explore the impact of an intergeneration reminiscence program onuniversity students. The intergenerational reminiscence program was designed to facilitate intergeneration communication among older people and university students in Malaysia. We recruited a total of 52 undergraduate students from Abnormal Psychology course for this study. They were required to complete at least four sessions of intergenerational interactions with an older adult as part of their coursework. At the end of intergenerational reminiscence activities, students developed a life history book for the interviewed older adult. Two focus groups were conducted for data collection. Three researchers were involved in the data collection and data analysis process. The findings from the thematic analysis show that the intergenerational reminiscence program was able to engage both older people and university students meaningfully. The impacts on university students include changes of perceptions, awareness of intergenerational difference, learning from older people, and meaningful for older people, and acquisition of new skills.
Keywords: Psychology; aging; Intergenerational reminiscence; thematic analysis; Malaysia